Pengaruh Kompetensi, Independensi, Profesionalisme, Dan Time Budget Pressure Terhadap Kualitas Audit Studi Empiris pada Kantor Akuntan Publik Kota Surakarta dan DIY - Setiawan, Alfin Wahyu; , Drs. Wahyono, MA, Ak (2016)
This study aimed to examine the effect of competence, independence, professionalism, and time budget pressure on audit quality. The population in this study is the auditors who work in public accounting firms Surakarta and Yogyakarta. The method of collecting samples by using purposive sampling technique. The sample used in this research is 66 respondents. Primary data collection method used is questionnaire method. The data are analyzed by using technical analyze Multiple Regression Analyze. The results showed that R2 values obtained 0.604 which means that 60.4% of audit quality is affected by the competence, independence, professionalism and time budget pressure. The remaining 39.6% influenced by variables outside the model. T test results showed that the professionalism and time budget pressure affect the quality of the audit results. While the competence and independence does not affect the quality of the audit results.